A New Way to Promote Islamization of Science: I-SETS Design for Pre-Service Science Teachers - Muhamad Imaduddin (Journal of Natural Science and Integration, 2020)
The development of science, especially natural science apart from religion ultimately raises a theological problem. The intersection between science and religion is contained in the National Curriculum respecting religious attitudes. Educators are expected to present meaningful integrated science to equip learners with skills to participate fully in society. This study aims to design an I-SETS (Islamic-Science, Environment, Technology, and Society) integrated learning for pre-service science teachers. The literature study was used in studying western and Islamic science, Golshani’s Islamization of science paradigm and I-SETS vision. The design is based on learning levels: I-SETS foundation, I-SETS issues awareness, I-SETS issues investigation, and action skills development. This design is expected to be an alternative raw model that will be applied by pre-service science teachers at various levels.